Knowledge and medicinal plants in El Ach region (Algeria) - Radjai, Aida; Sarri, Djamel; Zedam, Abdelghani (Ethnobotany Research and Applications, 2025)
Background: This ethnobotanical study intended to count the plants species according to their uses by people, whether as ethno-medicinal in the local traditional medicine, food or anything else in El Ach region southern Bordj-Bou-Arreridj (Algeria). Methods: The ethnobotanical data were collected in 2023 from 130 local informants through structured questionnaires and interviews, focusing on medicinal plant names, parts used, preparation methods, applications, and treated ailments. Quantitative analysis involved two indices, Use Value (UV) and Fidelity Level (FL), to assess data significance and reliability, while Non-Metric Multidimensional Scaling (NMDS) was used to explore the relationship between plant use and participants' socio-demographic characteristics. Results: An inventory recorded 53 medicinal plant species from 26 botanical families, with Asteraceae being the most represented (12 species), followed by Lamiaceae (7 species), and others having between 1 to 4 species each. Asteraceae species were widely used to treat various diseases using methods like decoction, compress, infusion, and powder. For example, Artemisia herba-alba asso with a fidelity level (FL) of 89.39%, is notably used to treat diabetes, stomach pain, colon issues. Additionally, Non-Metric Multidimensional scaling (NMDS) analysis showed significant relationships and differences in plant knowledge across different age groups. Conclusions: This research explores the rich ethnobotanical heritage of the El Ach community, revealing a wide variety of traditional medicinal plants used locally. It emphasizes the community's strong bond with nature and the importance of ethnobotanical studies in preserving indigenous knowledge for the future. Keywords: Ethnobotany, Medicinal Plants, Traditional Medicine, El Ach region, Algeria.